Modificação de semicondutores de Sb2Se3 com co-catalisadores de MoSx e Pt para a produção de hidrogênio verde via water splitting solar - Costa, Magno Barcelos (Universidade Federal de São Carlos, 2022)
Sb2Se3 semiconductors have been shown to be excellent photocathodes with attractive optoelectronic properties when compared to other photoabsorbers commonly used. However, its photocorrosion in aqueous media prevents it from reaching satisfactory rates of photoelectrochemical (PEC) conversion and requires further modifications to make its use viable. In the present work, two co-catalysts are investigated separately to verify their influence during PEC experiments, these being MoSx and Pt. MoSx was deposited with different deposition cycles and showed a photocurrent density (jph) between −0.6 and −5.7 mA cm−2 at −0.2 VRHE, that is, a maximum value of ~70× greater than the non-modified film. The result showed that the lower the number of cycles, the greater its photoresponse, since the effect of parasitic light absorption was present. In addition, there was a reduction in the number of charge carrier recombination in the surface states in the presence of MoSx. Pt deposition was performed by electrodeposition (ED) and photoelectrodeposition (FED). The FED method resulted in superior performance compared to that in the absence of light, reaching a value 3× higher than the ED method, i.e., a jph value of −1.4 mA cm−2 at 0 VRHE. This result was related to the greater number of Pt particles distributed on the semiconductor surface due to the increase in available sites for Pt deposition. In short, the presence of both co-catalysts was essential for Sb2Se3-based semiconductors to achieve considerable results and allow their use as a promising alternative in solar water splitting. While MoSx needed to be in a strongly acidic medium and at −0.2 VRHE, Pt proved to be a more energetically favorable and eco-friendly alternative (i.e., at 0 VRHE and at pH 6.5).
Sb2Se3-based semiconductors modified with MoSx and Pt co-catalysts for green hydrogen production via solar water splitting
Keywords: Sb2Se3; Hidrogênio; Catalisador; MoSx; Pt; Water splitting; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA